2020
DOI: 10.3389/fnagi.2020.599246
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-T199678 Mitigates α-Synuclein-Induced Dopaminergic Neuron Injury via miR-101-3p

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder characterized by dopaminergic neuron death and the abnormal accumulation and aggregation of α-synuclein (α-Syn) in the substantia nigra (SN). Although the abnormal accumulation of α-Syn can solely promote and accelerate the progress of PD, the underlying molecular mechanisms remain unknown. Mounting evidence confirms that the abnormal expression of long non-coding RNA (lncRNA) plays an important role in PD. Our previous study found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In this study, the result indicated that miR-101-3p was a potential downstream molecular target of lncRNA-T199678 (Bu et al, 2020b). Further investigation revealed that an overexpressed lncRNA-T199678 inhibited α-Syn-induced neuronal damage via regulating intracellular oxidative stress, cell cycle dysfunction, and apoptosis that was reversed by the miR-101-3p mimic (Figure 1) (Bu et al, 2020b). Therefore, an overexpressed lncRNA-T199678 ameliorated α-Syn-induced dopaminergic neuron injury by targeting miR-101-3p.…”
Section: Overexpression Of Lncrna-t199678 Alleviates α-Syn-induced Inmentioning
confidence: 64%
See 4 more Smart Citations
“…In this study, the result indicated that miR-101-3p was a potential downstream molecular target of lncRNA-T199678 (Bu et al, 2020b). Further investigation revealed that an overexpressed lncRNA-T199678 inhibited α-Syn-induced neuronal damage via regulating intracellular oxidative stress, cell cycle dysfunction, and apoptosis that was reversed by the miR-101-3p mimic (Figure 1) (Bu et al, 2020b). Therefore, an overexpressed lncRNA-T199678 ameliorated α-Syn-induced dopaminergic neuron injury by targeting miR-101-3p.…”
Section: Overexpression Of Lncrna-t199678 Alleviates α-Syn-induced Inmentioning
confidence: 64%
“…The striatum of patients with multiple system atrophy was observed to have an overexpressed miR-101 that was associated with α-Syn deposits, autophagy (Valera et al, 2017), inflammation (Han et al, 2019), oxidative stress, and apoptosis (Yi et al, 2019). In this study, the result indicated that miR-101-3p was a potential downstream molecular target of lncRNA-T199678 (Bu et al, 2020b). Further investigation revealed that an overexpressed lncRNA-T199678 inhibited α-Syn-induced neuronal damage via regulating intracellular oxidative stress, cell cycle dysfunction, and apoptosis that was reversed by the miR-101-3p mimic (Figure 1) (Bu et al, 2020b).…”
Section: Overexpression Of Lncrna-t199678 Alleviates α-Syn-induced Inmentioning
confidence: 68%
See 3 more Smart Citations